Vegetables Price Volatility in Poland – Onion and Carrot Case - Łukasz Zaremba (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
There are the producers who takes the weakest position on the agricultural market. Their activity is especially exposed to the risk factors. Price volatility which stays behind the price risk is one of the most important threats for producers’ incomes. Economic stability is a base for investment and development. That is why the price volatility is worth to having a look at. There are two species examined in this paper: onion and carrot. Both have a significant share in Polish vegetable production. Onion crops are mostly exported but carrot is being sold on the domestic market. Apart from the sales market there was no significant difference in analyzed period between farm-gate price volatility for both species. The measured volatility was getting lower in consecutive years of analyzed period; only in years of unfavorable weather conditions there were some growth. The analyze was conducted with usage of descriptive statistic on the logarithmic rates of return.